Systematic design analysis and risk management on nanoparticles occupational exposure - Silva, F., (2016)
Worker's health and occupational safety are critical to the development of nanotechnology applications, since some nanomaterials present a risk of adverse effect on human beings. This paper describes the application of the Systematic Design Analysis Approach based on the hazard process model (bow-tie) as well as design analysis of the production process, during a development project to produce a new type of ceramic tile with photocatalytic properties. Applying the bow-tie model together with the design analysis to the production process, it is possible to identify the emission and exposure scenarios and the related barriers based on the unit operations and the different technological options to perform them. Alternatives to the production process were considered, falling back on solutions to reduce emissions, and consequently the exposure to nanoparticles. The intervention model proposed will allow occupational safety and hygiene to be integrated into the development process that will involve a multidisciplinary team. Systematic Design Analysis Approach is a suitable method for occupational safety and hygiene risk management. This approach proved to be effective in generating relevant emission and exposure scenarios, as well as identifying possible barriers to control such emission scenarios.